Intimate Partner Violence, Maternal Gatekeeping, and Child Conduct Problems. Issue 5 (December 2016) - Zvara, Bharathi J.; Roger Mills‐Koonce, W.; Cox, Martha; ,
Abstract : We examined the mediating role of parenting behavior on the relationship between intimate partner violence and child conduct problems, as well as the moderating role of maternal gatekeeping to these associations. The sample ( N = 395) is from a longitudinal study of rural poverty in the eastern United States exploring the ways in which child, family, and contextual factors shape child development over time. Study findings indicate that a father's harsh–intrusive parenting behavior may be a key mediating pathway linking intimate partner violence and child conduct problems. Study findings further provide evidence for problematic outcomes for children when mothers encourage fathers with high levels of harsh–intrusive parenting to interact with their children.